2017
DOI: 10.1111/exd.13375
|View full text |Cite
|
Sign up to set email alerts
|

PKCι is a target of 7,8,4′‐trihydroxyisoflavone for the suppression of UVB‐induced MMP‐1 expression

Abstract: The soy isoflavone daidzein is bioconverted to 7,8,4'-trihydroxyisoflavone (7,8,4'-THIF) by microorganisms. Here, we investigated the matrix metalloproteinase (MMP)-1 inhibitory properties of 7,8,4'-THIF that arise through the suppression of UVB-induced MMP-1 expression. 7,8,4'-THIF reduced UVB-induced MMP-1 expression at the transcriptional level in primary human dermal fibroblasts and inhibited UVB-induced transcriptional activity of AP-1, a major activator of MMP-1 expression. Additionally, it was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Histological studies have shown that photoaged skin is associated with increased epidermal thickness and changes in the organization of connective tissue [26,50]. Similarly, we found that chronic UVB induced epidermal thickening in mouse skin, while PGG inhibited the increase in epidermal thickness.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Histological studies have shown that photoaged skin is associated with increased epidermal thickness and changes in the organization of connective tissue [26,50]. Similarly, we found that chronic UVB induced epidermal thickening in mouse skin, while PGG inhibited the increase in epidermal thickness.…”
Section: Discussionsupporting
confidence: 78%
“…Since elevated MMP-1 levels are closely associated with photoaging [28], we investigated the effects of PGG on UVB-induced MMP-1 expression in HaCaT cells. It has been well-reported that UVB strongly induced MMP-1 mRNA and protein level and subsequently MMP-1 was secreted into culture media in cell model systems [26,27,29,30]. In contrast, changes in MMP-2 mRNA and protein levels by UVB irradiation were not observed or very slightly increased in human keratinocytes [27,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated sUV exposure promotes matrix metalloproteinases (MMPs), the expression and activity which are regulated by AP‐1, a transcription factor activated by sUV irradiation (Wang & Dreesen, ). Of these AP‐1‐regulated MMPs, the collagenase MMP‐1 plays important roles in the degradation of type 1 and type 3 collagen within the skin (Lim et al, ). MMP‐1 is overexpressed after UV exposure, and it has been reported that the occurrence of skin wrinkles is alleviated when its expression is blocked (Han et al, ).…”
Section: Introductionmentioning
confidence: 99%